1993
DOI: 10.1007/bf00801745
|View full text |Cite
|
Sign up to set email alerts
|

Predicting maladjustment of exchange students in different cultures: a prospective study

Abstract: The aim of this study was to construct a discriminant function to predict maladjustment in foreign cultures for 123 Japanese adolescents studying abroad in home stay for 1 year. The maladjustment was defined in terms of self-reported friendship availability, friendship satisfaction and emotional distress. Among the variables assessed before departure, three factors emerged as strong predictors of maladjustment: neuroticism, maternal care before age 16, and friendship availability at home. The discriminant func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…On the other hand, neuroticism as a personality trait negatively predicted psychosocial adjustment to the U.S. This finding was also in line with research showing positive relationships between neuroticism and greater psychological adjustment problems (Furukawa & Shibayama, 1993;Ward et al, 2004) indicated by depression and social difficulty in student and expatriate samples. Married international graduate students who display features of anxiety, hostility, depression, impulsiveness and vulnerability (Costa & McCrae, 1992) could be at higher risk for experiencing psychosocial problems during their adjustment to the U.S.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, neuroticism as a personality trait negatively predicted psychosocial adjustment to the U.S. This finding was also in line with research showing positive relationships between neuroticism and greater psychological adjustment problems (Furukawa & Shibayama, 1993;Ward et al, 2004) indicated by depression and social difficulty in student and expatriate samples. Married international graduate students who display features of anxiety, hostility, depression, impulsiveness and vulnerability (Costa & McCrae, 1992) could be at higher risk for experiencing psychosocial problems during their adjustment to the U.S.…”
Section: Discussionsupporting
confidence: 87%
“…There are two shared predictors of both general and academic sociocultural adjustment supported by empirical evidence (Furukawand & Shibayama, 1993;Ryder, Alden, & Paulhus, 2000;Ward, et al, 2004). These are Openness to Experience, which is related to actively seeking new experiences and intellectual curiosity, and Neuroticism, which is related to maladaptive coping responses (John, et al, 2008).…”
Section: Personalities and Cross-cultural Adjustmentmentioning
confidence: 85%
“…Sociocultural adjustment could be facilitated by social learning and an adaptive coping style (Furukawand & Shibayama, 1993;Ward & Kennedy, 1999). There are two shared predictors of both general and academic sociocultural adjustment supported by empirical evidence (Furukawand & Shibayama, 1993;Ryder, Alden, & Paulhus, 2000;Ward, et al, 2004).…”
Section: Personalities and Cross-cultural Adjustmentmentioning
confidence: 91%
“…Furukawa and colleagues, for example, have indicated in a number of studies that variables such as neuroticism and emotion-focused coping predict adjustment and re-adjustment in Japanese sojourners and immigrants (Furukawa, 1997;Furukawa & Shibayama, 1993, 1994. The factors identified and measured by the ICAPS should work in conjunction with other cognitive variables identified by previous research as important in intercultural adjustment.…”
Section: Discussionmentioning
confidence: 99%